2019
DOI: 10.1101/847277
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SNP-CRISPR: a web tool for SNP-specific genome editing

Abstract: CRISPR-Cas9 is a powerful genome editing technology in which a single guide RNA (sgRNA) confers target site specificity to achieve Cas9-mediated genome editing. Numerous sgRNA design tools have been developed based on reference genomes for humans and model organisms. However, existing resources are not optimal as genetic mutations or single nucleotide polymorphisms (SNPs) within the targeting region affect the efficiency of CRISPR-based approaches by interfering with guide-target complementarity. To facilitate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…There are approximately 10–15 million common human SNVs, which can impact the efficacy of CRISPR/Cas9 editing ( Chen et al ., 2020 ; Eichler et al ., 2007 ). Since CROTON accurately predicts 1 bp insertion probability with the best performance ( Tables 1 and 2 ), we utilized 1 bp insertion probability to analyze the effect of SNVs on CRISPR/Cas9 editing outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…There are approximately 10–15 million common human SNVs, which can impact the efficacy of CRISPR/Cas9 editing ( Chen et al ., 2020 ; Eichler et al ., 2007 ). Since CROTON accurately predicts 1 bp insertion probability with the best performance ( Tables 1 and 2 ), we utilized 1 bp insertion probability to analyze the effect of SNVs on CRISPR/Cas9 editing outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…2020). Drury et al ., (2017) demonstrated that minor natural polymorphisms in target sites reduce gene drive effectiveness in flour beetles, and tools have been developed to help researchers design gRNAs accounting for population variation (Chen et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Gene drive mechanisms to eliminate D. suzukii have been experimentally tested on multiple lines to ensure the miRNAs are broadly effective (Buchman et al 2018), but a large dataset of wild population sequencing allow researchers to more confidently select target sites that are non-variable and thus nonresistant to Cas9 targeting (Schmidt et al 2020). Drury et al, (2017) demonstrated that minor natural polymorphisms in target sites reduce gene drive effectiveness in flour beetles, and tools have been developed to help researchers design gRNAs accounting for population variation (Chen et al 2020). Similarly, with the recent development of a CRISPR-Cas9 editing and RNAi knockdown protocols for D. suzukii (Murphy et al 2016;Li and Scott 2016;Taning et al 2016;Ahmed et al 2020), prior knowledge of allelic variation will allow researchers to design targeting oligonucleotides more precisely to avoid loci with variability.…”
Section: Despite Being Recently Established Invasive Populations Botmentioning
confidence: 99%
“…Although one should be careful to draw general conclusions from a single example, this result suggests that SNVs can induce unexpected off-target activity and that individual level genetic variation should be taken into consideration when designing gRNAs for medical purposes. Computational strategies that take into account SNVs in gRNA binding prediction already exist 42,43 , but those rely on databases that does not contain all variants that any individual carries. Our results further demonstrate that gRNAs can bind to genomic DNA despite having three or more single nucleotide mismatches, or even insertion or deletion mismatches.…”
Section: Discussionmentioning
confidence: 99%